Breeding Acrocomia aculeata for vegetative, phenological, reproductive and productive traits - Coser, Sara Morra (2016)
The study aimed to contribute to the characterization of Macaw Palm accessions from the Germplasm Bank of Macaw Palm in Federal University of Viçosa, in order to collaborate with the establishment of macaw palm breeding program and select potential accessions that meet characteristics to be aggregated to the final ideotype corresponding to the producer needs and demands of the potential markets for the species. Thus, the accessions were evaluated in two stages. In the first stage 52 accessions were evaluated for vegetative (HFS, DBH, AC), phenological (PREC) and reproductive (TS) characteristics, for diversity, estimation of genetic parameters and correlation study aiming selection of the superior accessions for these traits. Genetic diversity resulted in the formation of four groups by Tocher methodology coupled with the heritability values and coefficient of variation represented primordial diversity for the improvement of the species. Heritability in the narrow sense was classified as moderate (PREC, TS, CA) and high (HFS and DBH) magnitudes, and accuracy values were classified from moderate (PREC and CA) to high (TS, HFS and DBH). Selection of accessions for PREC, TS and HFS resulted in gains higher than 100% especially for accessions 36, 44 and 4 from Minas Gerais. In the second stage 36 accessions were evaluated for the traits precocity (PREC), first spathe height (APE), total number of fruits (NFT), pulp oil (TOP) and oil production per plant (PROD) through the estimation of genetic parameters and genetic correlation to proceed the prediction of breeding values to select the best individuals to compose the seed production population for a short-term program and the breeding population for a long-term program. The individual heritability and selective accuracy were classified as moderate magnitude for the traits PREC, NTF and PROD and high magnitude for APE and TOP, reflecting success and security in selection process. The highest correlation coefficients were found between the traits PREC and APE, PREC and NTF, and NTF and PROD, allowing indirect gains through selection of the simpler measurement trait. The selection of the top 20 individuals results in 74.8% gains over the average of PROD trait for a short-term seed orchand formation, since the selection of the top 52 individuals results in 40.5% gains for the formation of long-term breeding population. Considering the simultaneous selection through additive selection index with economic weights is possible to obtain direct gains from selection for PROD characteristic of 67.6%. This was the first study to evaluate these characteristics in a germplasm bank of macaw palm and our findings reveal essential genetic diversity for breeding programs combined with genetic parameters with excellent selective potential and gains with the selection, the basis for the success of the breeding program for the species with the establishment of seed production population for a short-term program and the breeding population for a long-term program and the development of cultivars with the ideotype demanded by the market.